2021
DOI: 10.1038/s41598-021-99001-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial community as impacted by addition of rice straw and biochar

Abstract: The application of straw and biochar can effectively improve soil quality, but whether such application impacts paddy soil bacterial community development remains to be clarified. Herein, the impacts of three different field amendment strategies were assessed including control (CK) treatment, rice straw (RS) application (9000 kg ha−1), and biochar (BC) application (3150 kg ha−1). Soil samples were collected at five different stages of rice growth, and the bacterial communities therein were characterized via hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…The results in Figures 2C, D indicate that the microbial community significantly decreased after being polluted with Cr(VI). Proteobacteria and Actinobacteria were the dominant phyla in all soil samples, consistent with other reports (31,32). The properties of Proteobacteria, a slightly acidic and metabolically diverse species, can explain the high presence of these in soil samples (33).…”
Section: Discussionsupporting
confidence: 90%
“…The results in Figures 2C, D indicate that the microbial community significantly decreased after being polluted with Cr(VI). Proteobacteria and Actinobacteria were the dominant phyla in all soil samples, consistent with other reports (31,32). The properties of Proteobacteria, a slightly acidic and metabolically diverse species, can explain the high presence of these in soil samples (33).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the BS microbial phyla were dominated by Proteobacteria and Chloroflexi . Both of them were often found as the main phyla in soils [ 51 , 52 ]. After the dairy manure application, the bacterial community structure in the soil was significantly changed by increasing the relative abundance of Firmicutes and Bacteroidetes , consistent with previous findings [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patescibacteria and Actinobacteriota have been suggested to induce plant root biomass and thus supporting better nutrient acquisition (63). Role of Chloroflexi in plant health is not clear although study has reported that Chloroflexi comprising anaerobic bacteria, are found to be enriched in paddy fields depending on oxygen availability and regulate soil bacterial community composition (64).…”
Section: Discussionmentioning
confidence: 99%